2016
DOI: 10.3892/mco.2016.1057
|View full text |Cite
|
Sign up to set email alerts
|

TP53 mutation is associated with a poor clinical outcome for non-small cell lung cancer: Evidence from a meta-analysis

Abstract: A number of studies have examined the association between tumor protein 53 (TP53) mutations and the clinical outcome in patients with non-small-cell lung cancer (NSCLC), although these have yielded conflicting results. In the present study, electronic databases updated to September 2015 were searched to find relevant studies. A meta-analysis was performed on the eligible studies, which quantitatively evaluated the association between the TP53 mutations and the survival of patients with NSCLC. Subgroup and sens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
74
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(80 citation statements)
references
References 44 publications
5
74
1
Order By: Relevance
“…Numerous studies demonstrated the role of TP53 mutations in predicting poor prognosis of advanced NSCLC patients [9,[11][12][13][14][15], and this was confirmed also in the subgroup of NSCLC patients carrying EGFR mutations [8,9,16]. In particular, different recent studies showed that the concurrent presence of TP53 mutations negatively affects response to TKIs in EGFR-mutated NSCLC patients, suggesting a role for these gene mutations in determining primary resistance to these drugs [6,7,[17][18][19][20].…”
Section: Discussionmentioning
confidence: 85%
“…Numerous studies demonstrated the role of TP53 mutations in predicting poor prognosis of advanced NSCLC patients [9,[11][12][13][14][15], and this was confirmed also in the subgroup of NSCLC patients carrying EGFR mutations [8,9,16]. In particular, different recent studies showed that the concurrent presence of TP53 mutations negatively affects response to TKIs in EGFR-mutated NSCLC patients, suggesting a role for these gene mutations in determining primary resistance to these drugs [6,7,[17][18][19][20].…”
Section: Discussionmentioning
confidence: 85%
“…Mutations in the TP53-gene represent another possible reason for differences in survival. TP53-mutations have been associated with a worse prognosis, and are less common in never-smokers [51,52]. A meta-analysis including 19 studies with a total of 1406 NSCLC patients with a TP53-mutation and 1965 patients without a TP53-mutation estimated a 26% higher overall survival for those lacking the mutation [52].…”
Section: Survivalmentioning
confidence: 99%
“…The technique of gene detection in most studies (11/15) was next generation sequencing (NGS) with which full genome profiling were conducted. Among all, 14 studies used tissue samples for gene detection [29][30][31][32][37][38]44,[46][47][48][49][50][51][52]58], except for study by Tsui DWY et al [47] in which blood samples were collected for gene detection.…”
Section: Characteristics Of the Included Studiesmentioning
confidence: 99%